Development of Career Adapt-Abilities Scale - Employee Selection (CAAS-ES) For Employee Selection Process - Ilyas Dzaky Almahdy; Hanisa Darupa Putri; Nawang Kusumastuti; Ocky Fajzar Suryani; Shah Hussain; Rizka Halida (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
This study aimed to develop the Career Adapt-Abilities Scale–Employee Selection (CAAS-ES) and examine its psychometric properties among Indonesian job seekers. Career adaptability refers to an individual’s ability to cope with career development tasks, work transitions, and changes that affect occupational roles. Assessing career adaptability in employee selection is important for identifying individuals’ readiness to navigate uncertainty and meet the demands of dynamic organizational environments. The CAAS-ES was developed based on Savickas’ theory of career adaptability and consists of 17 items measuring four dimensions: concern, control, curiosity, and confidence, using a six-point Likert scale. The respondents consisted of 290 job seekers aged 18–64 years. Data were analyzed using Confirmatory Factor Analysis (CFA) to examine construct validity and Cronbach’s alpha to assess reliability. The results indicated that the measurement model demonstrated an adequate fit to the data (CFI = 0.918, TLI = 0.901, RMSEA = 0.076, SRMR = 0.052) and excellent reliability (α = 0.92). These findings suggest that the CAAS-ES is a valid and reliable instrument for measuring career adaptability among Indonesian job seekers.Penelitian ini bertujuan untuk mengembangkan Career Adapt-Abilities Scale–Employee Selection (CAAS-ES) serta menguji kualitas psikometriknya pada populasi pencari kerja di Indonesia. Adaptabilitas karier merepresentasikan kemampuan individu dalam menghadapi tugas perkembangan karier, transisi pekerjaan, dan perubahan yang memengaruhi peran kerjanya. Pengukuran adaptabilitas karier dalam proses seleksi karyawan penting dilakukan untuk mengidentifikasi kesiapan individu dalam menghadapi ketidakpastian dan tuntutan organisasi yang dinamis. Alat ukur CAAS-ES dikembangkan berdasarkan teori adaptabilitas karier Savickas dan terdiri atas 17 item yang mengukur empat dimensi, yaitu concern, control, curiosity, dan confidence, menggunakan skala Likert enam poin. Responden penelitian ini terdiri atas 290 pencari kerja berusia 18–64 tahun. Data dianalisis menggunakan Confirmatory Factor Analysis (CFA) untuk menguji validitas konstruk, serta koefisien Cronbach’s alpha untuk menguji reliabilitas. Hasil analisis menunjukkan bahwa model pengukuran memiliki tingkat kecocokan yang memadai dengan data (CFI = 0.918, TLI = 0.901, RMSEA = 0.076, SRMR = 0.052) serta reliabilitas yang sangat baik (α = 0.92). Temuan ini menunjukkan bahwa CAAS-ES merupakan instrumen yang valid dan reliabel untuk mengukur adaptabilitas karier pada populasi pencari kerja di Indonesia.